Clinico-mycological study of onychomycosis in indian diabetic patients - Sonia Agrawal; Archana Singal; Chander Grover; Shukla Das; S V Madhu (Wolters Kluwer Medknow Publications, 2023)
Background: Onychomycosis (OM) is the most common nail disorder accounting for 40-50% of all onychopathies. Onychomycosis is caused by dermatophytes in majority, mostly Trichophyton (T.) rubrum followed by T. mentragrophytes var. interdigitale. However, there is a variation in the etiological profile with the subset of population, time, and geographical location. In immunocompromised hosts, non-dermatophytic molds (NDMs) and yeasts like Candida albicans and Candida parapsilosis are the main causative agents. Diabetes mellitus (DM) is a well-established risk factor for OM. Aim and Objectives: This study was conducted to determine the clinical and mycological characteristics of OM in diabetic patients and to evaluate the clinico-etiological correlation, if any. Materials and Methods: Three hundred consecutive diabetic patients were screened, of whom 102 (34%) patients were diagnosed with OM based on clinical, mycological, dermoscopic, and histological criteria. Results: Distal lateral subungual onychomycosis was the most common clinical variant seen in 80 (78.43%) patients. Fungal culture was positive in 57 (55.88%) of which NDMs constituted approximately half (47.61%) of the isolates, followed by Candida species (30.15%) and dermatophytes (22.22%). The clinico-mycological correlation was performed to look for the association of various fungi with the clinical type of OM. Distal lateral subungual onychomycosis was majorly caused by NDMs (51.02%), followed by Candida species (28.57%), and dermatophytes (20.40%). Conclusion: Non-dermatophytic molds are increasingly incriminated as the causative organisms for OM in DM and must be considered as potential pathogens in the present scenario, thus necessitating the change in the treatment options accordingly.